Teknologi Kecerdasan Buatan (Artificial Intelligence) Dan Penerapannya Di Perpustakaan - Miftha Khulzannah; Hilda Syaf’aini Harefa; Prabudi Darus (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2023)
This article reviews the use of artificial intelligence (AI) in libraries and provides some examples of its work. This article explains how libraries can use a variety of artificial intelligence applications to simplify work and improve user service. Any type of AI is coverage can be used in the library. As initiators and discussion partners for IT professionals, librarians help develop libraries by incorporating artificial intelligence into them. By applying AI in libraries, the library will be an unlimited source of knowledge, not only for the physical collections that fill the space in the libraries but also as a source of information in various forms.